Motives Of Murder Reflected In Paula Hawkins's The Girl On The Train Novel (2015): A Psychoanalytic Analysis - Ati, Karlena Widy, TitisSetyabudi, M.Hum (2017)
This research is purposed to reveal motives of murder in The Girl on the Train novel. The research describes how the psychological condition of the three main characters and to reveal the motives of murder reflected in the Girl on the Train novel. The type of this research is qualitative study. In analyzing this novel, the researcher uses Psychoanalytic analysis. The primary data source for this research is The Girl on the Train novel (2015) by Paula Hawkins. The secondary data of this research are taken from any information or all referential data related to the novel. The result of the research shows the different psychological condition of the three main characters, such as: (1). the psychological conditions of Rachel are a depression woman and psychological setback, (2). the psychological conditions of Megan are a traumatic woman and seducer, (3). the psychological conditions of Anna are a static and normal woman. Second, the researcher found the two case motives of murder in this novel such as: (1). Tom's motives to murder Megan, and (2) Rachel and Anna's motives to murder Tom.